Dialectics and transformation: An encounter between Moacir Gadotti and Karl Marx - Augusto Laranja, Mirza (2022)
Moacir Gadotti is one of the greatest critical thinkers of Brazilian education nowadays. His work has shown great potential to promote alternative political projects. The book Concepção Dialética da Educação was first published in 1983. As well as Dialectic in Marx reflects a conception of man and society, Gadotti is also clearly committed to the worker's point of view. These notes present his idea about dialectics throughout the history and his understanding that it stands out as a new instrument to fight for social justice in Latin America.